PENGARUH MEDIA SOSIAL TIKTOK TERHADAP PENGETAHUN DAN SIKAP REMAJA PUTRI TENTANG ANEMIA - Diah Elisma Febryanti; Sri Hazanah, Dian Ardyanti (CV. Adiba Aisha Amira, 2025)
Background: Anemia is a condition where there is insufficient iron in the body, either from food or iron supplements. There is still a significant prevalence of anemia among teenage females in Indonesia. Since teenage females shed blood on a monthly basis, they are more likely to have anemia than young men. Objectives: The purpose of this research is to examine how health education on TikTok has influenced the understanding and perspective of teenage girls at SMA Negeri 4 Samarinda about anemia. Metodes: This research method uses quantitative with one-group pretest-posttest design. The population was 10th grade students with a sample of 66 people, which was obtained from the calculation using the Slovin formula. Data analysis used on knowledge and attitude variables using the Wilcoxon test. Results: The results of univariate analysis showed that most respondents were characterized by 15 years of age, included in the category of non-risky menstruation, and had never been exposed to information about anemia. On the results of knowledge identification, respondents with good knowledge at pretest were 30 students and at posttest were 65 students. Meanwhile, the results of attitude identification obtained respondents with good attitudes at pretest as many as 32 students and at posttest as many as 63 students. The ρ-value of 0,000 (ρ < 0,05) indicates that the use of TikTok social media for health education had an impact on the knowledge and attitudes of the respondents, according to the findings of the bivariate analysis. Conclusion: The results of this study suggest that teenage girls' knowledge and attitudes around anemia may be influenced by health education campaigns conducted on TikTok.